IDENTIFICATION OF CAREER CHOICE MOTIVATIONS IN MEDICAL STUDENTS AND ITS ASSOCIATION WITH ACADEMIC PERFORMANCE AND GENDER; A CASE CONTROL STUDY - Kiran, Faiza; Irum, Shazia; Zahoor, Asiya (Pakistan Armed Forces Medical Journal, 2021)
Objective: To identify the reasons for choosing medicine as a career in medical students and find their association with gender and different academic performance. Study Design: Case control study. Place and Duration of Study: Shifa College of Medicine, Islamabad Pakistan, from 2015 to 2017. Methodology: A self-reported questionnaire was developed after thorough literature search and interviewing few students. All students who gave consent and filled questionnaire were included in the study. Students, who obtained less than 50% marks in professional examinations, were labelled as cases and those who passed were labelled as controls. Ratio of cases to controls obtained was 1:2. Data was analyzed using SPSS-23. Results: Total 225 students took part in the study. Half of both genders [M=55 (50%), F=61 (53%)] came into this field by their own choice. Male students chose medicine as a career mainly because they were more passionate [M=51(46%), F=38 (33%), pvalue = 0.03], wanted to honor their parents‟ wishes [M=35 (31%), F=28 (24%)], and used to find biology easier than math [M=19 (17%), F=14 (12%)]. Female students chose medicine as a career mainly because they had a misconception of relatively easier career growth in medicine [M=4 (3%), F=6 (5%)]. Conclusion: Most medical students in this private institute came into medicine of their own choice. However, passion, honoring parents‟ wishes and finding biology easier than math was more evident in failed students and male gender whereas females came with misconception of an easy career path in medicine.